Oncogene mutation profile predicts tumor regression and survival in locally advanced rectal cancer patients treated with preoperative chemoradiotherapy and radical surgery. Issue 7 (June 2017) - Peng, Jianhong; Lin, Junzhong; Qiu, Miaozhen; Zhao, Yujie; Deng, Yuxiang; Shao, Jianyong; Ding, Peirong; Zhang, Huizhong; Wan, Desen; Lu, Zhenhai; Pan, Zhizhong
Tumor response to preoperative chemoradiotherapy and postoperative survival differs among patients with locally advanced rectal cancer. The objective was to find correlations of mutated oncogenes and clinical outcomes in locally advanced rectal cancer. A total of 70 patients with preoperative preoperative chemoradiotherapy followed by radical surgery at a single cancer center between 2006 and 2012 were enrolled. Pretreatment tumor biopsy samples were assayed for 238 mutation hotspots harboring 19 oncogenes by time-of-flight mass spectrometry and OncoCarta Array. Oncogene mutations were found in 48.6% of patients (34/70). KRAS was the most frequent driver mutation, found in 35.7% of patients (25/70), followed by PIK3CA (14.3%), NRAS (5.7%), FLT3 (2.9%), and BRAF (1.4%). Multiple gene mutations were observed in eight patients (11.4%). Tumors with KRAS mutations responded poorly to preoperative chemoradiotherapy (p = 0.044). Patients with oncogene mutations had worse 3-year disease-free survival than those without mutations (67.2% vs 94.2%, p = 0.010). Patients with KRAS or RAS mutations had lower 3-year disease-free survival (68% vs 88.3%, p = 0.016; 65.5% vs 92.3%, p = 0.004, respectively) and 3-year overall survival (88% vs 95.4%, p = 0.020; 89.7% vs 94.9%, p = 0.036, respectively) than those without KRAS or RAS mutations. Oncogene mutation status affected tumor response to treatment and long-term survival in locally advanced rectal cancer.